Czy jesteśmy odpowiedzialni za nasze działania? - Seel, Gerhard (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The article discusses a responsibility game which is, in fact a ‘question-answer-game’. Firstly, the characteristic of the responsibility game is made. Secondly, the ontology of the responsibility game is settled. Thirdly, the causality of our intentions and the process of decision making are analysed in-depth. Fourthly, the importance of a decision criterion for the process of decisionmaking is proven; whereby, a definition of an action an agent is morally responsible for is finally formulated.